STRUCTURE POPULATION OF PINE WOOLLY ADELGIDS (Hemiptera : Adelgidae) IN PERUM PERHUTANI UNIT III, WEST JAVA AND BANTEN, KPH SUMEDANG - Noor Farikhah Haneda; Stevano J S Iriando; Laura Flowrensia (Jurnal Silvikultur Tropika, 2016)
Pinus boerneri as Pine Woolly Adelgids, emergence rapidly around Pinus Plantation in Indonesia has been reported since last decade. This pest causing dieback, defoliated branches, and even death to the tree. The aim of this study to investigate the population structure of pine wooly adelgid attack in Pine forest (Pinus merkusii) in Perum Perhutani Unit III, West Java and Banten, KPH Sumedang. This research important as consideration about the distribution of pine wooly adelgid stages in presumtive level of consequential damage. There were three part of Pine twigs (crown, middle, and lower) from 18 trees that positively attacked being collected. Later on, twigs diameter and number of each pine woolly adelgids stages (egg, nymph and imago) from every twigs part been observed. Result shows that imago as the dominant stage that infested in Pine forest in Perum Perhutani Unit III, KPH Sumedang. Damage level that effect by P. boerneri devided into two categories light infested and heavy infested.Key words : Hemiptera, Pine Woolly Adelgid, P. boerneri, Pest, P. merkusii